The very busy spider - Carle, Eric. (New York, N.Y. : Penguin Young Readers, an imprint of Penguin Group (USA) LLC, 2014)
The farm animals try to divert a busy little spider from spinning her web, but she persists and produces a thing of both beauty and usefulness.
1.3
K-3.
K-3
Keywords: Spider webs -- Juvenile fiction; Spiders -- Juvenile fiction; Spider webs -- Fiction; Spiders -- Fiction; Spider webs -- Fiction; Spiders -- Fiction; Readers (Elementary).